SCHOOL CONTEXT AND DANCE IN COLLECTIVE: CASE STUDY IN STATE COLLEGE MACHADO DE ASSIS - Oliveira, Tainã Silva (Cadernos de Educação Tecnologia e Sociedade, 2015)
This research of a case study in State College Machado de Assis - CEMA, in order to analyze the school context and the reality of this dance school. The research is linked to the Institutional Program Initiation Purse in Teaching - PIBID, performed by scholarship students of the Bachelor's Degree in Dance at the Federal Institute of Education, Science and Technology -IFG Goiás, Campus Aparecida de Goiânia - Goiás. From analysis of diagnostic, highlighted the need to investigate and analyze a project of this school, that it is the creation and actions of a dance group called Danç'art. The methodology of the research, theoretical and field, permeated by the study authors and researchers that supported and provoked reflections. Brings inherent notes related to the school context which helps to think about the dance by the bias of a critical overview. For greater understanding of the school context were made questionnaires for students, for dance teacher, teachers of other subjects besides the director and coordinators. These studies validate and enable greater understanding of the need for experience and expansion looks about the dance school. From the field research through observations and interviews applied by scholars, we can see a devaluation by managers and teachers from other areas, which unfolds into challenges and contradictions, so that actions aimed at dance to expand and efetivem critically and consistently. Another objective is to cause a provocation and investigate the reality of dance in this context, from the following questions: what prompted the dance teacher to create the group and what look professional regarding the teaching of dance? What is the perception and interest of students to participate and be part of the group? What is an interactive dance and what is its importance in the perspective of a group of dance? How to give the processes of teaching, creation and testing of the group? Understanding the design of this research that enables a reflection of the reality dance school is required. This research underpins such questions in order to bring about reflection and although is still in progress, these issues are launched to discuss this reality when it comes to dancing in CEMA. It is understandable therefore that the intention of this study is not to answer these questions ended, but allow other and new reflections about language and dance approach in the school context.